Use of register‐ and survey‐based measures of anxiety in a population‐based Danish cohort. (8th July 2021) - Osler, Merete; Rozing, Maarten Pieter; Wium‐Andersen, Ida Kim; Wium‐Andersen, Marie Kim; Dantoft, Thomas Meinertz; Fink, Per; Jørgensen, Martin Balslev; Jørgensen, Terese Sara Høj
Abstract: Objective: We explored the comparability of anxiety measures from register‐ and survey‐based data including analyses of prevalence and associations with selected psychiatric and somatic diseases. Methods: We measured anxiety using Danish registers (hospital diagnosis and anxiolytic drug prescriptions), self‐reports, symptom checklist (SCL) scores, and a clinical interview in 7493 adults with mean age 52 (SD 13.3) years who participated in a health survey between 2012 and 2015. We estimated the prevalence of anxiety, agreement between different measures and performed quantitative bias analysis. Results: The lifetime prevalence of hospital diagnosed anxiety, anxiolytic drug prescriptions, and self‐reported anxiety were 4.4%, 6.2%, and 5.1%, respectively, after adjusting for selective participation. The agreement between the different anxiety measures was low. Thus, 25% with an anxiety diagnosis and 20% with anxiolytic drug prescriptions also had a high SCL score. Anxiolytic drugs were the only measure significantly associated with higher odds of heart disease. Hospital diagnosis and self‐reported anxiety were associated with depression with odds ratio (OR) above 15, whereas anxiolytic drug prescriptions were less strongly associated (OR = 2.2(95% confidence interval: 1.26–3.91)). The risk estimates attenuated considerably when correcting for measurement error, whereas the ORs became slightly higher when the selective participation in the survey was accounted for. Conclusion: Anxiety diagnosed in hospitals and self‐reported anxiety showed low level of agreement but provide comparable results regarding frequency measures and associations with disease outcomes.